2014
DOI: 10.1152/advan.00096.2013
|View full text |Cite
|
Sign up to set email alerts
|

Supporting physiology learning: the development of interactive concept-based video clips

Abstract: THE ACCOMMODATION of diverse student learning approaches and maintenance of good academic outcomes are often difficult to achieve in university courses, particularly where large classes are concerned. These issues become even more significant when dealing with first-year students in science courses with high levels of factual and conceptual content (18). In this report, we describe the construction and use of pedagogically sound, yet inexpensive, video clips that can be used to support learning of physiology c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Nonetheless, practices occasionally need to be adequate according to the available resources and the structure of the laboratory/room/university, which has made professors use alternative methods of practical teaching (16,18) or other methods instead. Some inexpensive methods, such as the use of video clips (11), puzzles (17), and other games (4), can be interesting alternatives. All of these strategies require creative work and planning by the professor and also should be based on evidence to ensure that professors are improving the teaching process (14).…”
mentioning
confidence: 99%
“…Nonetheless, practices occasionally need to be adequate according to the available resources and the structure of the laboratory/room/university, which has made professors use alternative methods of practical teaching (16,18) or other methods instead. Some inexpensive methods, such as the use of video clips (11), puzzles (17), and other games (4), can be interesting alternatives. All of these strategies require creative work and planning by the professor and also should be based on evidence to ensure that professors are improving the teaching process (14).…”
mentioning
confidence: 99%
“…Furthermore, it was agreed upon shortening the length of the narration, supporting the environment with cute characters, integrating the content to daily life problems and eliminating the language errors for further interactive videos.The evaluation of interactive videos also indicated that these videos would improve the development of basic mathematical skills (problem solving, communication and reasoning) as well as some high-order thinking skills (predicting and critical thinking). Guy et al (2014) stated that the interactive video supports the learning by providing active learning at the participant side. According to the specialist participated to the study, these videos could be used in geometry and measurement, numbers and operations, algebra and data analysis learning areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Especially worthy of note was the use of real-life clinical and physiological scenarios to capture attention, motivate learners, and provide contextual relevance. Finally, and with regard to Gagné’s seventh and ninth events, the provision of immediate instructional feedback that addressed both the correct answer and the distractors, in contrast to simply an indication of whether the answer chosen is correct or incorrect, has been shown to be important to students and to promote both knowledge retention and transfer ( Moreno, 2004 ; Mason and Rennie, 2008 ; Guy et al. , 2014 ).…”
Section: Discussionmentioning
confidence: 99%